2012
DOI: 10.1002/adv.21331
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Monomer Structure on Real‐Time UV‐Curing Shrinkage Studied by a Laser Scanning Approach

Abstract: The very fast curing rate, low coating thickness (<100 μm), and a wide range of viscosity of ultraviolet (UV) systems hindered the study of UV-curing shrinkage. A recently developed laser scanning method provided a chance to directly measure the real-time (UV-curing shrinkage. The effect of monomer chain lengths (degree of ethoxylation), monomer functionality, and monomer type (acrylate vs. methacrylate) on the shrinkage rates and shrinkage of UV monomers was systematically investigated. The concentration of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…For di(meth)acrylate monomers the increase in the length of the spacer between two unsaturations led to higher final conversions because decrease in cross-link density enhances mobility of the system [78,79]. Similarly, for triacrylate monomers, for example, trimethylolpropane triacrylate (TMPTA) and ethoxylated TMPTA, final conversions increase with the degree of ethoxylation, for example, from about 45% for TMPTA to about 90% in the case of TMPTA containing 15 ethoxy groups [81] due to formation of less dense network. Similarly, for triacrylate monomers, for example, trimethylolpropane triacrylate (TMPTA) and ethoxylated TMPTA, final conversions increase with the degree of ethoxylation, for example, from about 45% for TMPTA to about 90% in the case of TMPTA containing 15 ethoxy groups [81] due to formation of less dense network.…”
Section: Effect Of Monomer Functionality and Structurementioning
confidence: 99%
“…For di(meth)acrylate monomers the increase in the length of the spacer between two unsaturations led to higher final conversions because decrease in cross-link density enhances mobility of the system [78,79]. Similarly, for triacrylate monomers, for example, trimethylolpropane triacrylate (TMPTA) and ethoxylated TMPTA, final conversions increase with the degree of ethoxylation, for example, from about 45% for TMPTA to about 90% in the case of TMPTA containing 15 ethoxy groups [81] due to formation of less dense network. Similarly, for triacrylate monomers, for example, trimethylolpropane triacrylate (TMPTA) and ethoxylated TMPTA, final conversions increase with the degree of ethoxylation, for example, from about 45% for TMPTA to about 90% in the case of TMPTA containing 15 ethoxy groups [81] due to formation of less dense network.…”
Section: Effect Of Monomer Functionality and Structurementioning
confidence: 99%
“…Generally, for ultrafast polymerization reactions, higher final degrees of conversion can be attained in cases where the volume shrinkage occurs over a much longer timescale than the chemical conversion . However, quantification of volume shrinkage using photo DSC is difficult, due to lesser amount of sample used for analysis . For the system containing the cross‐linker, the ultimate conversion on calculation was observed to be over 100%.…”
Section: Resultsmentioning
confidence: 94%
“…23 However, quantification of volume shrinkage using photo DSC is difficult, due to lesser amount of sample used for analysis. 24 For the system containing the crosslinker, the ultimate conversion on calculation was observed to be over 100%. Ward et al have observed that during the photocopolymerization of polyethylene glycol-based methacrylate and dimethacrylate, the ultimate conversion in certain cases has been calculated to be above 100%.…”
Section: Analyses Of Kinetic Parametersmentioning
confidence: 99%
“…It is supposed that the enhanced resin compatibility and high curing ratio of the proposed composites induce densely photocrosslinked network between reactive hybrid nanoparticles and matrix resins, leading to the improvement in the adhesion strength. Moreover, the methacrylate groups in the surface of nanoparticles offer high adhesive strength and low shrinkage compared to the acrylate groups [ 35 , 36 ]. Notably, the epoxy–acrylate composite including reactive aluminum oxide nanoparticles exhibited a relatively high adhesion strength due to the high UV and heat curing ratios compared to that of the composite with reactive silica nanoparticles.…”
Section: Resultsmentioning
confidence: 99%